MODERN BASIS OF CONTROLLED HYPOTENSION USING PROPOFOL UNDER ANESTHESIA FOR ENDOSCOPIC SINUS SURGICAL INTERVENTIONS. (World Bulletin of Public Health, 2023)
To date, the problem of the effectiveness of the use of propofol under anesthesia with controlled hypotension in endoscopic sinus surgery continues to be relevant. The main problem is that bleeding during the operation will interfere with the view, because of this, the procedure will take longer, increasing the risk of damage to nearby structures (eyes and brain). One method of reducing bleeding during general anesthesia is controlled hypotension, which involves deliberately lowering blood pressure below normal to improve the surgical site. However, lowering blood pressure carries risks such as permanent brain damage, delayed awakening, a blood clot in the brain, insufficient blood flow to the brain, and death. Propofol (an anesthetic given intravenously) and volatile anesthetics (given by inhalation) are alternative ways to lower blood pressure during the anesthetic period